Conductance and spectroscopic mapping of EDOT polymer films upon electrochemical doping. (23rd March 2020) - Wieland, Matthias; Malacrida, Claudia; Yu, Qiulin; Schlewitz, Claire; Scapinello, Luca; Penoni, Andrea; Ludwigs, Sabine
Abstract: This paper deals with the electrochemical doping of different poly(ethylenedioxythiophene) (PEDOT)-based active layers performed in an organic electrochemical transistor configuration through the mapping of in situ conductance trends during electrochemical doping and dedoping. The experiments are complemented by UV/Vis/NIR in situ spectroelectrochemistry in the wavelength range from 400 to 1600 nm, which allow monitoring of the development of the neutral and charged redox species. Both electropolymerized EDOT-based layers and solution-processed chemically synthesized PEDOT films are characterized. In addition to pure electropolymerized PEDOT (e-PEDOT), tris(4-(2, 3-dihydrothieno[3, 4-b][1, 4]dioxin-5-yl)phenyl) (TPA-EDOT3 ) is electrodeposited to generate highly branched networks of P(TPA-EDOT3 ). The solution-deposited PEDOT films contain poly(ethylenedioxythiophene):poly(styrenesulfonate) (PEDOT:PSS) with ratios of 1:2.5 and 1:6. Overall, we find that e-PEDOT and PEDOT:PSS(1:2.5) behave like classical conjugated polymers with a plateau-like conductance over a wide potential region. In contrast, PEDOT:PSS(1:6) and P(TPA-EDOT3 ) show rather bell-shaped conductance profiles. The mixed-valence conductivity model is used to interpret the experimental results in terms of the number of accessible redox states. We suggest that the bell-shaped conductance in the case of PEDOT:PSS(1:6) is caused by a high amount of PSS insulator that limits the inter-chain interaction between PEDOT moieties and in the case of P(TPA-EDOT3 ) by its distorted molecular architecture.